The Study of Relationship between Organizational Learning and Organizational Performance - Azizi, Bisotoon (Revista Administração em Diálogo - RAD, 2017)
The aim of this study was to investigate the relationship between organizational learning and organizational performance among companies operating in the insurance industry of Tehran in Iran. The present study is a descriptive one in terms of the purpose and the method of data collection. The statistical population of the study was all insurance companies in the city of Tehran and 120 insurance companies were selected due to the lack of detailed statistical reference to their number. For this purpose, people were asked some questions who it was authorized to represent the name. The questionnaire is a tool for collecting data. The Gomez questionnaire et al. (2005) was used to measure organizational learning which includes four factors: management commitment, system perspective, openness and experimentation, transfer and integration of knowledge. To measure the organizational performance, the Yang et al. questionnaire (2004) is used. To determine the validity of data collection, the questionnaire was presented to six professors of management at various universities. The validity of questionnaire through the coordination of jury was about %100. The reliability of the questionnaire was conducted on thirty subjects, Cronbach alpha coefficient was calculated 0.91 and 0.85 for organizational learning and organizational performance, respectively. For data analysis, Pearson correlation coefficient and multiple regressions were used. The results showed that there is a positive relationship between organizational learning and its four dimensions (management commitment, vision systems, open space, and experimentation, transfer and integration of knowledge) and organizational performance of Tehran insurance companies.